Pengembangan Media Pembelajaran Video Animasi Pada Materi Larutan Penyangga Terintegrsi Nilai Islam - Sri Gustianty (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research was instigated by the lack of animation video learning media that integrated Buffer Solution lesson with Islamic values. This research aimed at developing animation video learning media on Islamic values and knowing validity and practicality levels. It was Research and Development (R&D) with 4-D (Define, Design, Develop, and Disseminate) model which is limited to the Develop stage. This research was administered at State Senior High School 12 Pekanbaru. The object of this research was animation video learning media on Islamic values integrated Buffer Solution lesson. The subjects were material experts, media experts, Islamic integration experts, Chemistry subject teachers, the twelfth-grade students of MIPA 1. This research produced three animation video soft files with a duration of 13 minutes 05 seconds and a file size of 27,78 MB on the first video; 24 minutes 45 seconds and a file size 44,03 MB on the second video; and 11 minutes 53 seconds and a file size of 24.37 MB on the third video. The percentages of validation result were 95% by material experts with very valid criterion, 92.86% by media experts with very valid criterion, and 90% by Islamic integration experts with very valid criterion. The percentage of practicality test result by Chemistry subject teachers was 94.74% with very practical criterion, and the percentage of student response test result was 92.36% with very good criterion.